Pengaruh Perilaku Konsumtif, Media Sosial, dan Religiusitas terhadap Keputusan Pembelian Konsumen pada E-Commerce Shopee (Studi pada Mahasiswa UIN STS Jambi) - Yanti, Novita Damai; Rafidah, Rafidah (ALSYS, 2025)
This study is motivated by the increasing trend of online shopping among university students, influenced by various factors. However, there remains a lack of research that simultaneously examines the relationship between consumptive behavior, social media, and religiosity in shaping purchasing decisions on e-commerce platforms. The objective of this research is to analyze the influence of these three variables on the purchasing decisions of students at UIN Sulthan Thaha Saifuddin Jambi on the Shopee platform. A quantitative approach was used with a correlational survey design. The sample consisted of 99 students selected purposively and proportionally using the Slovin formula and stratified random sampling technique. Data were collected through a validated and reliable online Likert-scale questionnaire. Data analysis was conducted using SPSS version 26, involving classical assumption testing, multiple linear regression, t-tests, F-test, and coefficient of determination. The findings show that, partially, consumptive behavior, social media, and religiosity each have a positive and significant effect on purchasing decisions. Simultaneously, the three variables also significantly affect purchasing decisions, with an F-value of 40.705 > F-table value of 2.70 and a significance level of 0.00 < 0.05. This study contributes to the growing body of literature on digital consumer behavior through the lens of religiosity and offers practical insights for developing relevant marketing strategies in the e-commerce era.